Drug Prescribing Pattern During Intranatal Period in a Secondary Care Hospital in South India - Deepasree Sukumaran; Anne George Cherian; Saibal Das; Blessed Winston A; Aniket Kumar; Margaret Shanthi FX (SAGE Publishing, 2016)
Background: During delivery, drugs being prescribed cause concerns due to their harmful effects on lactation as well as potential adverse reactions on the mother. This retrospective study was performed to evaluate the drug prescribing pattern during normal delivery in a secondary care hospital in India. Materials and Methods: This cross-sectional retrospective study included 3 months of patient's medical records. Results: A total of 2222 drugs, comprising 51 different types of drugs were prescribed to 313 mothers undergoing normal delivery. Most of these drugs are safe in lactation. Ten types of drugs would have been better avoided, but they possibly did not cause harm because of their limited short-term use only during the intranatal period. Conclusion: This study reflects a good, safe, and rational medication practice during normal delivery for various common ailments in a secondary care hospital and can be cited as an example for similar settings.